Detection of cotton seed oil in cow ghee using Triglyceride profiling (Indian Journal of Dairy Science, 2023)
The triglyceride profiling of ghee shows significant variations in different regions of India, influenced by factors such as feeding practices, fatty acid composition, lactation stage, and season. Our study focused on detecting and identifying ghee adulterated with cottonseed oil and ghee sourced from the cotton tract area. Triglyceride profiling was employed on pure, adulterated, and cotton tract area ghee samples. Our findings revealed consistent lower levels of triglycerides with carbon numbers C24 to C30 in cow ghee, while higher levels were observed for carbon numbers C38 to C40 and C50 to C54. However, in ghee adulterated with cottonseed oil, triglycerides with carbon numbers C34 to C38 significantly increased (p